(untitled) (Research, Society and Development, 2020)
The objective of this paper is to identify similarities between ISO management systems standards with the intention of management systems integration using the cognitive computing and review of international scientific literature. The Google Scholar and CORE databases were consulted, and the research period was from 2015 to 2019. This is a longitudinal, exploratory and descriptive research that used a review of technical and scientific literature and cognitive computing. Fifty-six publications addressing ISO management systems were selected, in accordance with the terms: standardization, similarity and integration. There is opportunity for studies to develop framework for integrated management systems, standardization and integration of management systems certification.